Severe forms of hereditary spherocytosis in children with congenital active cytomegalovirus infection - A. A. Komarova; H. A. Sarkisyan H. A.; A. P. Khokhlova; E. A. Polyak; V. A. Vershinnikova; K. R. Baltaeva; D. R. Kantserova; V. A. Mironova; L. M. Makarova; A. L. Belaya; A. E. Atapina; I. G. Lyubeznova (LLC "Diagnostics and Vaccines", 2024)
Congenital cytomegalovirus (CMV) infection is the cause of fetal malformations, fetal death, severe generalized disease up to death, and changes in hematopoiesis. It should be noted that the pantropic effects of the virus and the peculiarities of the immunopathogenesis of congenital CMV infection are often the basis for the occurrence of autoimmune diseases Also CMV can be the reason in decompensation of combined pathologies. Below are two cases of severe hereditary sphero-cytosis in children with congenital active CMV infection.